Peran Hukum Pidana dalam Menanggulangi Lone-Wolf Terrorism dan Tantangan dalam Penegakan Hukumnya - M. Akendra Pasha; Sofa Laela (LPPM Iblam School of Law, 2025)
Lone-wolf terrorism has become an increasingly significant threat due to its unpredictable nature and the difficulty in detecting perpetrators before they commit acts of terror. Unlike organized terrorist groups, lone-wolf terrorists operate independently, making it challenging for law enforcement to identify early warning signs. The rise of digital platforms has further facilitated self-radicalization, allowing individuals to adopt extremist ideologies without direct contact with terrorist networks. This phenomenon presents legal and security challenges that require an adaptive criminal law approach. This study employs a qualitative method with a normative legal approach, focusing on regulatory analysis and the interpretation of legal norms in current practices. Data collection is conducted through literature review, utilizing primary legal sources such as laws and court decisions, as well as secondary sources like academic journals and previous research. The findings indicate that while Indonesian criminal law provides a legal foundation for countering terrorism, it faces significant obstacles in addressing lone-wolf terrorism. Challenges include difficulties in early identification, limited evidence collection, and legal gaps in dealing with individuals who show signs of radicalization but have yet to commit crimes. Strengthening preventive legal frameworks, integrating advanced technology in monitoring radicalization patterns, and enhancing inter-agency cooperation are crucial steps to improving law enforcement effectiveness against lone-wolf terrorism. The study highlights the need for a balanced legal strategy that ensures national security without compromising human rights.